DEVELOPING ENGLISH LEARNING MATERIAL FOR SPEAKING SKILL BASED ON ADDIE - Palupi, Fitri (Premise: Journal of English Education and Applied Linguistics, 2017)
The main objective of the research is to develop speaking English materials based on ADDIE (Analysis, Design, Development, Implementation and Evaluation). This Research was conducted at SMP N 5 Metro, which is located at Rejomulyo 26 B/RT.22 RW VI, South Metro. The type of research that was conducted by the researcher is developmental research. Research is not meant to generate a theory or verify one. It attempts to develop English learning material for speaking skill for ADDIE (analysis, design, development, implementation and evaluation) at first semester of seventh grade.  In this research, the researcher uses Design Instructional model as the research design. It aims to develop English learning material for speaking skill. The result of developing vocabulary material is in the form of multimedia power point presentation. The researcher has passed some steps in developing the English vocabulary material; Need Analysis, Design, Development, Expert Validation, Try Out, Revision, and Final Product. It could be as a proof that this material could be applied to the seventh-grade students. In revision, the researcher still had to revise the product to be easier also smaller bytes so that this product could be used for the seventh-grade students of SMP N 5 Metro. After having revision, the final product has been ready to be applied. In conclusion, learning material for speaking skill based on ADDIE could be applied to the seventh-grade students.